Short-term effects of Venezuelan immigration in Peru - Valdiglesias Oviedo, Jhon (2019)
The article reaffirms the positive effects of immigration in the long term, however, with the intention of emphasizing the problems that arise in the short term, regarding the recent Venezuelan immigration in Peru. These problems derive due to the characteristics of the economy, as well as the nature of a large informal sector or the deficit of physical capital and public infrastructure. It is worth to note that the duration of these problems will depend on the quality of the public policies that will be implemented to achieve the benefits of immigration. Finally, some policy recommendations are proposed.